Pattern recognition third Mexican Conference, MCPR 2011, Cancun, Mexico, June 29 - July 2, 2011 : proceedings - Martínez Trinidad, José Francisco (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the Third Mexican Conference on Pattern Recognition, MCPR 2011, held in Cancun, Mexico, in June/July 2011. The 37 revised full papers were carefully reviewed and selected from 69 submissions and are organized in topical sections on pattern recognition and data mining; computer vision and robotics; image processing; neural networks and signal processing; and natural language and document processing.